PENGARUH KOMPETENSI, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KUALITAS LAYANAN PADA DINAS PENDAPATAN, PENGELOLA KEUANGAN DAN ASET DAERAH KOTA PALU - Nurhayati, Nurhayati (Katalogis, 2015)
The objectives of this research are to know and analyze the effects of competency, discipline and work environment simultaneously and partially on service quality at Regional Office of Income, Financial Management and Asset Palu City. Population of the of this research covers 5.756 tax payers. Out of those tax payers, 98 samples have been calculated using Slovin equation. Analysis technique used in this research is multiple linear regressions. The results show that competency, discipline and work environment simultaneously perform positive and significant effects on service quality at Regional Office of Income, Financial Management and Asset Palu City. Partially, the result also shows that competency, discipline and work environment perform positive and significant effects on service quality. Determination coefficient which is indicated by adjusted R square 0.472 meaning that 47,2% service quality in Regional Office of Income, Financial Management and Asset Palu City is affected by competency, discipline and work environment and 52,8% is affected by other variables that are not investigated in this research.